Racial Discrimination, Black Identity, and Critical Consciousness in Spain - Cea D’Ancona, M.ª Ángeles (Race and social problems, 2023)
This article analyzes the relationship of racial discrimination on the identity and critical consciousness of 1369 African and Afro-descendant respondents to the first nationwide survey conducted in Spain in 2020. The survey not only showed the scope of experiences of discrimination based on skin color but has also opened the way for testing whether these experiences of racial discrimination end up affecting the identity and critical consciousness of black people, Africans, or Afro-descendants, based on the questions included in the survey and the rejection–identification hypothesis. According to the statistical models obtained by discriminant analysis, racial discrimination helps to strengthen racial identity. Having been discriminated by skin color was the variable that most differentiated those who self-identified with their country of origin from those who did not and the second most predictive of self-recognition as a black or Afro-descendant person. But when the influences of racial discrimination on racial identity and critical consciousness were jointly analyzed, applying structural equation modeling, the latter outweighed the former: racial discrimination contributes to the awakening black activism. Less clear seems to be the influence of racial identity on critical consciousness.